A influência de períodos de lockup sobre o desempenho das cotas de fundos multimercados brasileiros - Pontes, Gleison de Abreu (2016)
Most of investment funds has the advantage of shares liquidity. For that reason, managers of some types of funds may find it difficult to maintain the position of their portfolios and provide higher returns to their investors quota. Some evidences on edge funds suggest that quota performance is positively affected by establishing larger time intervals before investors realize the rescue of their applications, called as lockup periods. Therefore, by selecting from a sample of 165,386 observations from 2009 to 2014 formed by the monthly net returns of 4,667 hedge funds that resemble the investment strategies of hedge funds in the United States, this research aimed to analyze whether lockup periods influence Brazilian multimarket funds quotes. By using econometric models, we tested this policy imposition under three forms allied to other variables in literature such as fund age, size of fund liquid equity, management fees and performance fees on investment funds in quotas. It was possible to predict the share performance in hedge funds in the period selected for this study. Results suggest the existence of lookup award in the Brazilian scene only when this variable is estimated by a dummy or values range, which indicates that using this policy may help Brazilian multimarket fund managers to keep their investment portfolios and provide greater profitability to quotas. This fact corroborates some previous studies in USA hedge funds context. Furthermore, finding lockup award for the category of hedge funds brought implications for the Efficient Market Hypothesis (EMH), for Agency theory and also to the field of Behavior Finances. For EMH the evidences suggest the existence of market inefficiencies in Brazilian context, in the semi-strong form propagated by this theory. For Agency Theory, this study provides evidence that conflicts of interest between shareholders and hedge fund managers can be mitigated by imposing periods of lockup. To Behavior Finances the results stimulate the investigation of present bias, by demonstrating the possibility of existing investors considered as sophisticated in this category of investment funds. Concerning to control variables we found the influence on the share profitability in hedge funds for characteristics related to fund age, fund size of the equity and management fees. This study shows that lockup periods can contribute in obtaining better indicators of profitability in the financial market.